Robotically Assisted Medial Reduction Osteotomy: A Technique Based on the Pythagorean Theorem - Bono, Olivia J.; Wester, Christopher; Bono, James V. (The Journal of Knee Surgery, 2025)
Varus deformity can present a significant challenge for limb alignment correction and balancing in total knee arthroplasty (TKA). One technique to address these challenges is a medial reduction osteotomy. This article describes utilization of a robotic platform to perform a safe and accurate medial subtraction osteotomy prior to balancing and bony resections. Deformity correction can be predicted by the Pythagorean Theorem. Computed tomography-based robotic systems can be used to perform medial reduction osteotomy of the tibia in the setting of significant varus deformity in patients undergoing TKA. Prior to balancing and bony cuts, the tibial component is downsized “virtually” from the planned size. Through lateralization of the component, the excess medial bone can be mapped via tracking of the registration probe and removed. The amount of medial tibial bone resected determines the amount of laxity that will be created when the tibia is reduced under the femur when implants are placed. Following this, soft tissue tensioning, planning, bony resections, and trialing can progress as normal for a robotic total knee. Through the described technique, the authors have been able to predict the amount of coronal plane correction based on the size of the osteotomized fragment using the Pythagorean Theorem. Robotic guidance of a medial subtraction osteotomy provides a safe and predictable means of varus correction. This is beneficial in that it can be performed with great accuracy and prior to any further balancing maneuvers or bony cuts.
Keywords: robotic TKA; medial reduction osteotomy; balancing